2004
DOI: 10.2527/2004.821129x
|View full text |Cite
|
Sign up to set email alerts
|

Energy requirements of cattle for standing and for ingestion, estimated by a ruminal emptying technique1

Abstract: Energy requirements for ingestion and standing were determined in open-circuit respiration chambers with four ruminally cannulated German Red Pied steers weighing 617 +/- 53 kg of BW (mean +/- SD). The requirement for standing over lying was derived by regressing heat production on time spent standing within 2-h periods when no feed was offered to avoid any interference with eating activity, and amounted to 14 kJ/(d x kg of BW). The energy requirement for ingestion was determined by calculating the difference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 13 publications
4
12
1
Order By: Relevance
“…Steers offered a grass silage-based diet were observed eating more often than those offered a wholecrop silage-based diet, which, in turn, were observed eating more often than those offered high-concentrate diets (Walsh et al, 2008a,b). Susenbeth et al (2004) found that the time required by steers to consume 1 kg grass silage DM was 26 min, whereas consumption of 1 kg DM rolled barley required 8 min. Unlike current study, Kelly et al (2010a) and Basarab et al (2011), using beef heifers offered whole-crop silage and concentrates, found no effect of RFI on total feeding duration.…”
Section: Animal Performance and Body Compositionmentioning
confidence: 97%
See 1 more Smart Citation
“…Steers offered a grass silage-based diet were observed eating more often than those offered a wholecrop silage-based diet, which, in turn, were observed eating more often than those offered high-concentrate diets (Walsh et al, 2008a,b). Susenbeth et al (2004) found that the time required by steers to consume 1 kg grass silage DM was 26 min, whereas consumption of 1 kg DM rolled barley required 8 min. Unlike current study, Kelly et al (2010a) and Basarab et al (2011), using beef heifers offered whole-crop silage and concentrates, found no effect of RFI on total feeding duration.…”
Section: Animal Performance and Body Compositionmentioning
confidence: 97%
“…Susenbeth et al (1998) estimated that for low-quality roughage, the energy cost of eating accounted for approximately 26.5% of ME intake. Susenbeth et al (2004) found that the energy cost of eating 1 kg DM of rolled barley was only 23% of that required to ingest 1 kg DM of grass silage. Thus, activity associated with eating, particularly forage diets, may explain some of the unaccounted variation in RFI.…”
Section: Introductionmentioning
confidence: 98%
“…However, whether the association with digestion and RFI is an inherent efficiency or mainly related to a higher passage rate of digesta due to intake is unclear. Susenbeth et al (2004) found that cattle consumed an additional 19.2% kJ/kg of BW when standing than they do when lying, showing that animals' physical activity influences energy expenditure and feed efficiency. Similar to the findings of Lawrence et al (2011a), results from this study 'indoors' suggest that differences in physical or locomotion activity between high and low RFI groups does not noticeably contribute to variation in phenotypic RFI.…”
Section: Lawrence Kenny Earley and Mcgeementioning
confidence: 99%
“…In the present study, all of the feed ingredients were finely ground, hence the mouse deer did not spent much time on chewing and ruminating. Susenbeth et al (2004) clearly demonstrated that activity of eating and chewing is the dominant factor causing increased HP during ingestion rather than the nature of feed in cattle. It has been reported previously that HP of the mouse deer was related to physical activity like eating, standing or sitting.…”
Section: Tablementioning
confidence: 95%
“…Previous study had shown that heat production of mouse deer was influenced by factors like activities (eating, standing and sitting) and sex of the animals (Darlis et al 2001). It is not known whether levels of dietary fiber would influence heat production in mouse deer, although it has been reported that energy requirement for eating and chewing represents a considerable proportion of the total energy metabolism in ruminants and other herbivores than feed composition (Susenbeth et al 2004 It is hypothesized that mouse deer would show little difference between the MRT of small particles and solute and digestibility parameters would be affected by different levels of fiber in the diet. In this study, pellets containing varying levels of fiber were prepared to evaluate feed intake, nutrient digestibility, MRT of particles and solute and heat production of mouse deer.…”
Section: Introductionmentioning
confidence: 96%